Association between CDK4 expression and overall survival of osteosarcoma patients - Dwi Tirtasari, Faizah; Arsyad Hakim, Fikar; Mathan Sakti, Yudha; Lukman Anwar, Sumadi; Gandi Bawono, Rheza; Kus Dwianingsih, Ery (Published by Universitas Gadjah Mada, 2024)
Osteosarcoma is the most common primary bone tumor malignancy, accounting for 30 - 80% of all primary bone tumors. It is presented in a bimodal distribution manner with the age of onset divided into two groups, 10-20 and >60 y.o. Various factors have significance in the patient's prognosis, including the expression of cyclin-dependent kinase 4 (CDK4). This CDK4 has an essential role in the pathogenesis of osteosarcoma through inactivation of the Rb gene, which is associated with the patient's survival. This study was conducted to evaluate the correlation between CDK4 expression and the survival of osteosarcoma patients. It was a cross-sectional study involving 50 patients diagnosed with osteosarcoma based on clinical, radiological, and histopathological examination. Available formalin-fixed paraffin-embedded (FFPE) samples were retrieved for immunohistochemical (IHC) staining of CDK4. The survival data was collected from medical records. CDK4 expression and survival data were analyzed statistically using the Kaplan-Meier curve. Out of 50 subjects, CDK4 was found to be expressed in 38 samples (76%). The group with negative CDK4 showed a slightly longer overall survival (by 0.2 mo) than the positive CDK4 group. However, these results were not statistically significant (p = 0.821). In conclusion, the overexpression of CDK4 may not directly affect the survival rate in osteosarcoma. Other factors need to be considered to understand the complexity of the disease.